2010
DOI: 10.3109/08958370903521224
|View full text |Cite
|
Sign up to set email alerts
|

Refractory ceramic fiber (RCF) toxicity and epidemiology: A review

Abstract: This paper provides a review of the relevant literature on refractory ceramic fibers (RCFs), summarizing relevant data and information on the manufacture, processing, applications, potential occupational exposure, toxicology, epidemiology, risk analysis, and risk management. RCFs are amorphous fibers used for high-temperature insulation applications. RCFs are less durable/biopersistent than amphibole asbestos, but more durable/biopersistent than many other synthetic vitreous fibers (SVFs). Moreover, as produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 168 publications
0
36
0
Order By: Relevance
“…The latency period for pleural plaques related to asbestos exposure is typically reported as 15-40 years (ACC Review, 2004;British Thoracic Society, 2011;Chapman et al, 2003;Hillerdal, 1981Hillerdal, , 1994Utell & Maxim, 2010). However, Larson et al (2010) reported a much reduced latency (median 8.6 years, range 1.4-14.7 years) for pleural plaques associated with exposure to LAA.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The latency period for pleural plaques related to asbestos exposure is typically reported as 15-40 years (ACC Review, 2004;British Thoracic Society, 2011;Chapman et al, 2003;Hillerdal, 1981Hillerdal, , 1994Utell & Maxim, 2010). However, Larson et al (2010) reported a much reduced latency (median 8.6 years, range 1.4-14.7 years) for pleural plaques associated with exposure to LAA.…”
Section: Introductionmentioning
confidence: 96%
“…With very few exceptions (Cramond & Casserly, 2006;Hilt et al, 1987;Mukherjee et al, 2000;Myers, 2012) investigators have concluded that most subjects with pleural plaques are nearly always asymptomatic (Ameille & Letourneux, 1999;Broderick et al, 1992;Christen et al, 1997;Crane et al, 2005;Crapo, 2005;Dweik & Mazzone, 2010;Fishwick & Barber, 2014;Hillerdal, 1997Hillerdal, , 2001Hillerdal & Henderson, 1997;IIAC, 2008;Järvholm & Larsson, 1988;Jones, 1997;Meirelles et al, 2005;Mohr, 2012;Montes et al, 2005;Park et al, 2011;Roach et al, 2002;Rubin, 1986;Utell & Maxim, 2010). For example: Broderick et al (1992) studied an asbestos exposed population of sheet metal workers and examined the relationship between circumscribed plaque and four symptoms; dyspnea upon hurrying or walking up a slight hill (DOE), dyspnea worse than peers while walking (DSP), chest pain and cough.…”
Section: Pleural Plaques and Respiratory Symptomsmentioning
confidence: 99%
“…Asbestos production and trade is prohibited in some countries, while others have maintained or increased production and use in recent years. Substitution of asbestos by artificial fibers would not necessarily lower or eliminate health risks [10][11][12][13]96,97]. The increased incidence of malignant Mt in developed nations [98,99], despite the prohibition of asbestos, is probably at least in part due to improved diagnostics, an increasing awareness of Mt, a screening effect in asbestos-exposed populations, and some over-diagnosis in conditions with an unclear demarcation of malignant Mt as an entity.…”
Section: Resultsmentioning
confidence: 99%
“…It can be spontaneous, or occur when asbestos fibers are present in the pulmonary or pleural tissues. Apart from asbestos, other potential etiologic factors of malignant Mt are mineral (erionite) and artificial (ceramic, carbone nanotubes) fibers [10][11][12][13], virus SV40, radiation, and genetic predisposition [14][15][16][17] (Figure 2). …”
mentioning
confidence: 99%
“…From animal studies, it has been shown that inhalation of RCF produced fibrosis and pleural tumours [2]. However, the experiment protocols were criticised and it has been hypothesised that a lung overload effect occurred in these studies [3].…”
Section: Introductionmentioning
confidence: 99%